Root resorption in clear aligner treatment detected by CBCT: a Systematic review and Meta-analysis - Patadanai Butsabul; Pimsiri Kanpittaya; Ratichanok Nantanee (Elsevier, 2024)
Objective: The aim of this study was to evaluate the amount of external apical root resorption in patients who had undergone orthodontic treatment with clear aligners evaluated using cone beam computed tomography. Methods: Studies that evaluated external apical root resorption before and after comprehensive orthodontic treatment with clear aligners were assessed by performing an electronic search from 5 databases comprising PubMed, SCOPUS, EBSCO, Cochrane Library, and LILACS and manual searches in the relevant journals and the reference lists of the included studies. Database search, elimination of duplicate studies, and data extraction were performed independently by 2 authors. The quality of the included studies was assessed using the Risk of Bias in Non-randomised Studies-of Interventions and the Cochrane Collaboration's Risk of Bias Tool. Studies that reported the tooth length or volume were used for quantitative analyses. Results: Nine studies were included in the meta-analysis. The overall root length after clear aligner treatment was significantly decreased compared with the pre-treatment length using cone beam computed tomography (mean differences = −0.56 mm, 95% confidence interval [−0.73, −0.38], P < .00001). However, only the maxillary central incisors, maxillary lateral incisors, and mandibular central incisors had significant reduction in root length. The meta-analysis from 3 studies also indicated that the root volume of the upper incisors also significantly decreased (mean differences = −13.34 mm3, 95% confidence interval [−16.57, −10.10], P < .00001). Conclusions: Current evidence suggests that clear aligners can cause minimal root resorption. The highest amount of root resorption was observed in the maxillary central incisors.